Sensation seeking, risk behaviors and alcohol consumption among Mexican origin youth - Wilkinson, Anna V. (2011)
PURPOSE: To examine factors associated with ever use of alcohol among Mexican origin youth. METHODS: Using a prospective study design, we followed 1053 Mexican origin adolescents. Participants completed two surveys in their homes and three follow-up telephone interviews, every six to eight months, in between. The second home survey was completed 30 months (SD=4.8 months) after baseline. Acculturation, subjective social status, and family cohesion were assessed at baseline and final home visit. Ever drinking, risk behaviors, and sensation seeking tendencies were assessed at the final home visit only. RESULTS: Overall, 30% of the study participants reported ever drinking alcohol. Multivariate models revealed that being female, increasing age, lower levels of acculturation, family cohesion and subjective social status, higher sensation seeking tendencies and concomitantly engaging in three or four other risk behaviors were associated with ever drinking. Also, social disinhibition, an aspect of sensation seeking, mediated the relationship between engaging in other risk behaviors and alcohol use. This is consistent with previous research, suggesting that social disinhibition is a common factor that underlies the use of alcohol, tobacco, illicit drugs, and other problem behaviors. CONCLUSIONS: The results of this study support taking a family-based approach to prevention that includes discussion of other risk behaviors, especially smoking, among Mexican origin youth. In addition, tailoring programs by gender, directly addressing both how changes in social norms resulting from acculturation can impact a youth’s decision to drink alcohol and underlying gender-based differences in why youth drink could improve the efficacy of preventive interventions.